2018
DOI: 10.3390/molecules23092211
|View full text |Cite
|
Sign up to set email alerts
|

Residue Depletion of Florfenicol and Florfenicol Amine in Broiler Chicken Claws and a Comparison of Their Concentrations in Edible Tissues Using LC–MS/MS

Abstract: Antimicrobial residues might persist in products and by-products destined for human or animal consumption. Studies exploring the depletion behavior of florfenicol residues in broiler chicken claws are scarce, even though claws can enter the food chain directly or indirectly. Hence, this study intended to assess the concentrations of florfenicol (FF) and florfenicol amine (FFA)—its active metabolite—in chicken claws from birds that were treated with a therapeutic dose of florfenicol. Furthermore, concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…20 In the second research, the depletion of florfenicol (FF) and florfenicol amine (FFA) was studied. 12 For OTC and 4-epi-OTC, the concentration in claws 3 days after ceasing treatment was 2997 μg/kg. FF and FFA were determined in claws 5 days post-treatment at the level of 651 μg/kg, while doxycycline in the presented study was found at the concentration of 3505 μg/kg 4 day after the last antibiotic dose.…”
Section: ■ Results and Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…20 In the second research, the depletion of florfenicol (FF) and florfenicol amine (FFA) was studied. 12 For OTC and 4-epi-OTC, the concentration in claws 3 days after ceasing treatment was 2997 μg/kg. FF and FFA were determined in claws 5 days post-treatment at the level of 651 μg/kg, while doxycycline in the presented study was found at the concentration of 3505 μg/kg 4 day after the last antibiotic dose.…”
Section: ■ Results and Discussionmentioning
confidence: 94%
“…11 Chile reported the exportation of 14 990 tons of chicken claws in 2014. 12 Nowadays, an upward trend in the trade of this product is still observed. 11 Considering that claws have become a highprofit export byproduct for the poultry sector, attention should be paid to the presence of antimicrobial residues.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Not long ago, [62] identified FF and FFa residues in broiler chicken feathers up to day 40 after ceasing treatment, detecting concentrations that exceeded 100 μg/kg. Similarly, [63] detected them in chicken claws up to day 25 after ceasing treatment. Thus, the fact that these residues could be identified in our work up to day 10 after ceasing treatment might be a consequence of such prolonged bioaccumulation within feathers and claws, as well as the rapid excretion of these metabolites [64].…”
Section: Discussionmentioning
confidence: 99%